2010
DOI: 10.1039/c002541k
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented parallel packing of unsymmetrical bolaamphiphiles driven by π–π stacking of cinnamoyl groups

Abstract: The self-assembly and molecular packing mode of a novel, unsymmetrical bolaamphiphile, sodium 4-(6-hydroxyhexyloxy) cinnamate (SHHC) was studied. Tube-like structures were obtained in SHHC aqueous solution at pH 9.2. Upon UV irradiation, the SHHC molecules in the system were found to undergo four-center-type photocyclodimerization and photoisomerization. The combination of IR, XRD and Zeta potential results suggested the formation of a tail-to-tail type bilayer membrane structure: the SHHC molecules stretched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…11. As for 14-4-14 or C 12 E n /14-4-14, the four periodic reflection peaks suggest the existence of well-defined lamellar structures [52,53]. According to the Bragg equation, the layer spacing is about 2.42 nm, which indicates that bilayer aggregates are formed, and further confirms that the large aggregates observed by CryoTEM and TEM are vesicles.…”
Section: Aggregates Morphologysupporting
confidence: 67%
See 1 more Smart Citation
“…11. As for 14-4-14 or C 12 E n /14-4-14, the four periodic reflection peaks suggest the existence of well-defined lamellar structures [52,53]. According to the Bragg equation, the layer spacing is about 2.42 nm, which indicates that bilayer aggregates are formed, and further confirms that the large aggregates observed by CryoTEM and TEM are vesicles.…”
Section: Aggregates Morphologysupporting
confidence: 67%
“…9 and 10, respectively. It has been established that self-assembled structures of amphiphiles can be well preserved in casting films [52]. In order to determine the structural features of the aggregates, the cast films of the surfactant solutions has been prepared and measured by XRD, and the patterns are shown in Fig.…”
Section: Aggregates Morphologymentioning
confidence: 99%
“…19 This indicated that 2‐NA formed a cyclobutane structure in the gel. Meanwhile, the appearance of a bending vibration of the saturated C‐H of the cyclobutane at $\tilde \nu $ =1441 cm −1 in the spectrum of the 2‐NA precipitate (Figure S5) verified the topochemical reaction 20. The FTIR bands thus provided two indications for the occurrence of the [2+2] cycloaddition reaction: loss of the trans ‐vinylene CC bond and the appearance of cyclobutane.…”
Section: Resultsmentioning
confidence: 75%
“…Meanwhile, the appearance of a bending vibration of the saturated C-H of the cyclobutane at ñ = 1441 cm À1 in the spectrum of the 2-NA precipitate ( Figure S5) verified the topochemical reaction. [20] The FTIR bands thus provided two indications for the oc- currence of the [2+2] cycloaddition reaction: loss of the trans-vinylene C=C bond and the appearance of cyclobutane. Unambiguous evidence for the existence of the dimer was further provided by the MALDI-TOF data ( Figure S6), which showed a peak at m/z = 1682.7 for the precipitate, exactly corresponding to the dimer of 2-NA.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Moreover, a new absorption of the bending vibration of saturated C−H of the cyclobutane at 1342 cm −1 appears after photoirradiation, thus verifying the photodimerization in the gel. By using the CH 2 symmetrical stretching vibration band at 2850 cm −1 as a reference, we could estimate the degree of photodimerization as about 29 % upon analysis of the integral area of the C=C vibration band, which is slightly higher than that from the NMR spectra. It is reasonable that the higher temperature could possibly cause the transformation from dimer to monomer.…”
Section: Methodsmentioning
confidence: 99%